2003
DOI: 10.1638/03-077
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Peafowl (Pavo Cristatus) for Potential Pathogens at Three Michigan Zoos

Abstract: Blood samples collected from 31 free-roaming peafowl from three zoos in Michigan were tested serologically. Antibody titers were present against avian adenovirus and Bordetella avium in 19.3% and 61.3% of the samples, respectively. Serum plate agglutination tests were positive for Mycoplasma meleagridis and Mycoplasma synoviae in 3.2% and 38.7% of the samples, respectively. All birds were seronegative for avian influenza, Newcastle disease virus, West Nile virus, Mycoplasma gallisepticum, Salmonella pullorum, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 5 publications
2
15
0
1
Order By: Relevance
“…According to the literature, there is only one survey in pet birds where the prevalence of each intestinal parasite population was examined in parallel [8]. Some published studies included case reports [911] or surveys on a single parasitic agent [12, 13], while others examined intestinal parasites in a limited range of zoo species [1416]. Only a few coprological surveys were carried out in a wide range of avian species displayed at zoo settings [1720].…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, there is only one survey in pet birds where the prevalence of each intestinal parasite population was examined in parallel [8]. Some published studies included case reports [911] or surveys on a single parasitic agent [12, 13], while others examined intestinal parasites in a limited range of zoo species [1416]. Only a few coprological surveys were carried out in a wide range of avian species displayed at zoo settings [1720].…”
Section: Introductionmentioning
confidence: 99%
“…None of these evaluations involves cranes. Studies focusing on the bacterial flora of birds have concentrated primarily on the presence of abnormal bacterial species and possible outbreaks of disease [Maeda et al, 2001;Hiett et al, 2002;Hollamby et al, 2003;Waldenstrom et al, 2002]. To assess the possible role of bacterial flora in disease, as well as to determine the relative importance of bacteria that are found within diseased specimens, an understanding of what is typically present in healthy individuals is required [D'Aloia et al, 1996].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the above, very little is known about the incidence of Bordetella avium in populations of wildlife birds. A US study revealed that Bordetella avium can affect mallards, Canada geese, wild turkeys and birds kept in Zoos (Hopkins et al 1990, Raffel et al 2002, Hollamby et al 2003.…”
Section: Introductionmentioning
confidence: 99%